Crime, Employment and Social Welfare: an Individual-level Study on Disadvantaged Males - Geert Mesters; Victor van der Geest; Catrien Bijleveld (Tinbergen Institute, 2014)
We test economic and sociological theories for the relationship between employment and crime, where social welfare is used as an identifying mechanism. We consider a sample of disadvantaged males from The Netherlands who are observed between ages 18 and 32 on a monthly time scale. We simultaneously model the offending, employment and social welfare variables using a dynamic discrete choice model, where we allow for state dependence, reciprocal effects and time-varying unobserved heterogeneity. We find significant negative bi-directional structural effects between employment and property crime. Robustness checks show that only regular employment is able to significantly reduce the offending probability. Further, a significant uni-directional effect is found for the public assistance category of social welfare on property offending. The results highlight the importance of economic incentives for explaining the relationship between employment and crime for disadvantaged individuals. For these individuals the crime reducing effects from the public assistance category of social welfare equivalent to those from employment, which suggests the importance of financial gains. Further, the results suggest that stigmatizing effects from offending reduce the future employment probability.
Keywords: K42; C32; C33; 330; dynamic discrete choice; strain; social control; state dependence; reciprocal; unobserved heterogeneity